Large cell neuroendocrine carcinoma (LCNEC) of the urinary bladder: a case report - Colarossi Cristina; Pino Piero; Giuffrida Dario; Aiello Eleonora; Costanzo Rosario; Martinetti Daniela; Memeo Lorenzo (BMC, 2013)
Abstract Neuroendocrine carcinoma of the urinary bladder is a rare entity, accounting less then 1% of urinary bladder malignancies. The vast majority of the neuroendocrine carcinoma of the urinary bladder is represented by small cell neuroendocrine carcinoma while just few cases of large cell neuroendocrine carcinoma (LCNEC) have been reported. In this cases report we describe a rare case of primary bladder LCNEC. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2474700528951562.